O uso de amostrador artesanal para o estudo do equilíbrio químico: uma ferramenta para o ensino de química - Ferreira, Cesar Bernardo (2012)
This paper reports the process of producing an educational tool to be used by teachers of secondary and tertiary levels. The practice teaching practical lessons were developed on the subject ionic balance, as a means of motivating and triggering practical activity. The objectives of this work are to explore the potential of a learning object (Didactic Acqua sampler) through a video on the subject ionic balance aimed at teachers in the area of chemical and biological sciences, to make an analysis of the textbooks adopted for teaching by PNLEM chemistry, ionic balance of the topic, describing how to produce the sampler Acqua Didactic and use it didactically; assess the chemistry and biology teachers in high school realize the potential of the sampler for the Acqua Didactic teaching of ionic balance through a video. The methodology used was to record a video that covers issues related to the teaching of ionic balance, along with a demonstration of how to build and use the Guided Sampling Acqua. Collecting data on the questionnaire answered by teachers who evaluated the video from an educational standpoint. The results show that the obstacles to teaching and learning the various contents of chemistry is also presented for the topic chemical equilibrium. Since the books adopted by the National Textbook Program for high school, still need to improve their language.